2020
DOI: 10.1002/ecy.2969
|View full text |Cite
|
Sign up to set email alerts
|

Demography of snowshoe hare population cycles

Abstract: Cyclic fluctuations in abundance exhibited by some mammalian populations in northern habitats (“population cycles”) are key processes in the functioning of many boreal and tundra ecosystems. Understanding population cycles, essentially demographic processes, necessitates discerning the demographic mechanisms that underlie numerical changes. Using mark–recapture data spanning five population cycles (1977–2017), we examined demographic mechanisms underlying the 9–10‐yr cycles exhibited by snowshoe hares (Lepus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 78 publications
(167 reference statements)
3
21
0
Order By: Relevance
“…Although the conditions necessary for cycling to occur are understood and can be demonstrated mathematically, the specific drivers of cyclicity are diverse and vary within and among species. Endogenous factors include variations in reproductive output and other inherited qualities [ 12 ] or genetic drift [ 13 ], while exogenous factors include interactions with predators [ 14 ], diseases [ 15 ], food availability [ 16 , 17 ], and physical impacts, such as fires and floods [ 18 ]. Dispersal dynamics and social behaviors also influence the shape of cycles [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the conditions necessary for cycling to occur are understood and can be demonstrated mathematically, the specific drivers of cyclicity are diverse and vary within and among species. Endogenous factors include variations in reproductive output and other inherited qualities [ 12 ] or genetic drift [ 13 ], while exogenous factors include interactions with predators [ 14 ], diseases [ 15 ], food availability [ 16 , 17 ], and physical impacts, such as fires and floods [ 18 ]. Dispersal dynamics and social behaviors also influence the shape of cycles [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potentially cyclic population dynamics have been documented in small populations of temperate ungulates in fragmented ranges [ 19 ], but given the altered nature of these populations, it is difficult to assess whether these represent cases of cycling in the same way documented for snowshoe hares ( Lepus americanus ) [ 14 , 17 ] and small rodents such as lemmings and voles [ 20 ], given the reduced size of the populations and the fragmented nature of their range.…”
Section: Introductionmentioning
confidence: 99%
“…We validated a noninvasive method for measuring gestagen metabolites as indicators of different states of pregnancy in female mountain hares and showed variations in a population of free-ranging mountain hares over a period of six years. These results are important for understanding how the timing of the mountain hare reproduction period varies from year to year [ 32 ]. They also improve the interpretation of faecal glucocorticoid results when collecting “anonymous” faeces in free-ranging populations during reproductive periods.…”
Section: Discussionmentioning
confidence: 99%
“…Snowshoe hares (Lepus americanus) similarly undergo cyclic fluctuations in abundance, and manipulation experiments have demonstrated that these cycles are primarily driven by fluctuating predation risk (Krebs et al, 2018). The same type of CMR analysis in wild populations of snowshoe hares indicated that both survival and recruitment were related to cycle phase (Oli et al, 2020). Ultimately, survival and recruitment rates in hares are likely both a consequence of the same extrinsic factor: predation.…”
Section: Year Effects and Delayed Density Dependencementioning
confidence: 98%